THE HISTORY OF DETERMINING TIME AT NIGHT USING NOCTURLAB INSTRUMENTS - Hamas, Nuril Fathoni (Al-Hilal: Journal of Islamic Astronomy, 2024)
At night, determining time is a little more complicated because the Sun cannot be observed directly. However, there is a unique instrument for knowing the time at night by reference to the position of the stars in the sky, namely the nocturlab. This article will discuss the history of determining the time at night with nocturlab. The method used in this research is qualitative to get an overview of Nocturlab in the past. This research shows that the Nocturlab instrument has a long development history; even though it is now a more sophisticated tool for determining time, this tool remains an essential part of astronomy and determining time in human civilization.